1974
DOI: 10.1037/h0037105
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effects of three counselor verbal responses on client verbal behavior.

Abstract: The study determined the effects of four counselor stimulus conditions on three measures of client verbal behavior. The counselor stimulus conditions were reflection of feeling, probe, confrontation, and unspecified responses. The three dependent variables were client affect words, self-referent pronouns, and present verb tense. Twenty subjects were assigned randomly to one of four trained experimenters (counselors) for a 42-minute session. The first 2 minutes were a preliminary orientation period. The remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The observed frequencies, expected frequencies and the proportions which the observed frequencies represent for complementary one-up and noncomplementary one-up transactions for each of the three counselors are presented in Table 6. The obtained chi-square value was significant, x 2 (2) = 37.876, p < .001, allowing for rejection of the hypothesis that these counselors of different theoretical orientations did not differ in their proportion of one-up responses.…”
Section: Research Questionmentioning
confidence: 89%
“…The observed frequencies, expected frequencies and the proportions which the observed frequencies represent for complementary one-up and noncomplementary one-up transactions for each of the three counselors are presented in Table 6. The obtained chi-square value was significant, x 2 (2) = 37.876, p < .001, allowing for rejection of the hypothesis that these counselors of different theoretical orientations did not differ in their proportion of one-up responses.…”
Section: Research Questionmentioning
confidence: 89%
“…In contrast, in comparing reflection, restatement, and responses in which the counselor repeated verbatim feelings previously discussed by the client ("you feel ..."), Merbaum and Southwell (1965) reported that reflection significantly increased client affective responding, restatement significantly decreased responding, and repeating feelings had no significant effect. Highlen and Baccus (1977) found no differences between the effect of reflections and probes on client discussion of feeling, nor did Barnebei, Cormier, and Nye (1974) in comparing reflections, probes, confrontations, and mixed responses. In the only study involving interpretive responses, Auerswald (1974) found that these responses significantly increased client productivity of affect, while restatement significantly decreased selfreferent affect.…”
mentioning
confidence: 90%
“…Three of the above studies also examined client preferences for different counselor verbal responses, but none reported any significant differences (Auerswald, 1974;Barnebei et al, 1974;Highlen & Baccus, 1977). Reisman and Yamakowski (1974) compared friends' preferences for helping responses and found that expository responses (giving expert analysis or explana-tion) and mixed responses (a combination of empathic, interrogative, and expository responses) were perceived by friends as being more desirable than either empathic or interrogative responses.…”
mentioning
confidence: 99%
“…A possible answer to the problem of appropriate verbal conveyance can be sought in the actual verbal techniques employed by various counselors. Numerous studies have been conducted using counselor restatement (Hill & Gormally, 1977;Lavelle, 1977;Snyder, 1945) and reflective (Barnabei, Cormier, & Nye, 1974;Bergman, 1951;Helner & Jessell, 1974;Hill & Gormally, 1977;Lavelle, 1977), interpretive (Helner & Jessell, 1974;Lavelle, 1977), confrontive (Barnabei et al, 1974;Kaul, Kaul, & Bednar, 1973;Reece & Whitman, 1962), and supportive (Knight & Bair, 1976;Samaan & Parker, 1973) statements. _The findings, to date, do not clarify which technique or combination of techniques produce client change.…”
Section: Southern Illinois Universitymentioning
confidence: 99%